THE EFFECT OF POLITICAL POWER ON BUDGET MONITORING: A Study of Fertilizer Industry in Indonesia - Syakhroza, Akhmad (Gadjah Mada International Journal of Business, 2004)
This study examines the role of political power on the process of budget monitoring in the context of the fertilizer manufacturing industry in Indonesia. The objectives of this study are: (a)to investigate the relationship between budget monitoring and managerial roles, (b) to examine the two-way interaction effect between budgets monitoring and politics on managerial roles, and (3)to identify the effect of departmental power on the two-way interaction between budgets monitoring and politics affecting managerial roles. The sample for this study consists of four public sector fertilizer-manufacturing enterprises in Indonesia. This study uses a questionnaire survey supplemented by structured interviews. The questionnaire, adapted from previous studies, utilizes a seven-point Lilcert scale. Respondents to the questionnaire were middle managers. The results provide substantial evidence that interaction between budget monitoring and politics affect managerial roles; and that the departmental power plays a significant role on such interactions.